(3TQM GdTGWHjIs - (3Ydj Hf YKeGf Hf eMeO Hf MSfs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf CSgd eGEdi Yde GdbQGAGJ ai GdJUGfja GdefXheGJ fXe GdTjN GdEeGe GdYGde CHj eMeO bGSe Hf ZjQg GHf CHj GdbGSe Nda Hf CMeO GdOYjfi Ke GdTGWHi s
(3BNQgG (B:s
(3hgj TLQI cHjQI HLHd dHfGf hQbgG jTHg Ohf GNJdGa eSJWjd Hjf GdUaQI hGdNVQI gPG BNQ GdcJGH hGddg Gdehab ddUhGH s
(3GdfSNI HgG MhGTs
(3Ydjg Jedc HGSe YdGA GdOjf GdUHGZ GdTGaYi GdbGOQi GdXGgQis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdbQGAGJ hGdJLhjOs